2014
DOI: 10.1126/science.1255288
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated phospholipids facilitate membrane deformation and fission by endocytic proteins

Abstract: Phospholipids (PLs) with polyunsaturated acyl chains are extremely abundant in a few specialized cellular organelles such as synaptic vesicles and photoreceptor discs, but their effect on membrane properties is poorly understood. Here, we found that polyunsaturated PLs increased the ability of dynamin and endophilin to deform and vesiculate synthetic membranes. When cells incorporated polyunsaturated fatty acids into PLs, the plasma membrane became more amenable to deformation by a pulling force and the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
321
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(346 citation statements)
references
References 49 publications
(14 reference statements)
19
321
1
5
Order By: Relevance
“…Although these data strongly implicated cholesterol as the major lipid involved in cytotoxicity, we cannot exclude that other lipids were indirectly affected in these experiments. A reduction in the cholesterol levels at the plasma membrane might reflect differences in the composition of specific lipid microdomains targeted through GP, for example, polyunsaturated phospholipids resulted in deformations of the plasma membrane 52 , and phosphatidylserine levels in the cytoplasmic leaflet might also be affected.…”
Section: Resultsmentioning
confidence: 99%
“…Although these data strongly implicated cholesterol as the major lipid involved in cytotoxicity, we cannot exclude that other lipids were indirectly affected in these experiments. A reduction in the cholesterol levels at the plasma membrane might reflect differences in the composition of specific lipid microdomains targeted through GP, for example, polyunsaturated phospholipids resulted in deformations of the plasma membrane 52 , and phosphatidylserine levels in the cytoplasmic leaflet might also be affected.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that the rigid structure of SiNPs, perhaps paired with electrostatic interactions of their positively charged surface with negatively charged glycolipids lining the lumenal face of lysosomal membranes (32), may prevent membrane remodeling processes that are required for SNARE-mediated fusion with late endosomes or autophagosomes (33). Consistent with this possibility, it has been observed that membrane fission at the plasma membrane is regulated by the specific lipid environment (34). However, other mechanisms of SiNP action on lysosomal fusion cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…It is conceivable that ablation of Lpcat3 may reduce the incorporation of polyunsaturated PCs in the enterocyte plasma membrane with a consequent increase in membrane rigidity, which may perturb endocytosis and protein recruitment to the plasma membrane and ultimately lead to defective lipid uptake and secretion. Indeed, intestinal cholesterol absorption is mediated by endocytosis of NPC1L1 (28), and change in the composition of polyunsaturated PCs affects the endocytosis process (29,30).…”
Section: Discussionmentioning
confidence: 99%